2014
DOI: 10.1007/s11010-014-2306-x
|View full text |Cite
|
Sign up to set email alerts
|

Activation of oxidative stress and inflammatory factors could account for histopathological progression of aflatoxin-B1 induced hepatocarcinogenesis in rat

Abstract: Aflatoxin-B1 (AFB1) intoxication is known to develop hepatocellular carcinoma (HCC). However, pathogenesis and diagnosis of AFB1-induced HCC remain undefined. This article describes histopathological progression versus kinetics of the placental glutathione S-transferase (GST-pi) expression and profiles of the antioxidant enzymes, pro-inflammatory cytokines, and proliferative cell nuclear antigen (PCNA) in the liver from the rats administered with two doses of 1 mg AFB1/kg b.w. Histopathologically, hepatocytes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
39
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 54 publications
1
39
0
4
Order By: Relevance
“…Nrf2 antioxidant responses occur after exposure to other liver toxins including aflatoxin (Kensler et al 2014; Merrick et al 2012; Singh et al 2015) and carbon tetrachloride (Chen et al 2014), and are found in other organ toxicities including in the lung (Cho et al 2015) and nasal cavity (Dunnick et al 2015). …”
Section: Discussionmentioning
confidence: 99%
“…Nrf2 antioxidant responses occur after exposure to other liver toxins including aflatoxin (Kensler et al 2014; Merrick et al 2012; Singh et al 2015) and carbon tetrachloride (Chen et al 2014), and are found in other organ toxicities including in the lung (Cho et al 2015) and nasal cavity (Dunnick et al 2015). …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, inflammation and ROS generation are now evident to go hand to hand in a number of pathological manifestations, wherein, TNF-α has been found to play a regulatory role [35,36]. In case of brain disorders also, neuroinflammation and excitotoxicity have been found to be responsible for triggering neuro-excitotoxic disorders/diseases like; traumatic brain injury, Ischemia, Alzheimers disease, Parkinson's disease, etc [17,[37][38][39][40][41][42][43][44][45][46][47].…”
Section: Discussionmentioning
confidence: 99%
“…The anomers of the AFB 1 -FAPY-DNA adduct block DNA replication or cause mutations in Escherichia coli (Smela et al, 2002;Brown et al, 2006) and in vitro (Lin et al, 2014). Metabolically active AFB 1 can also indirectly damage DNA through oxidative stress (Shen et al, 1995;Bedard and Masey, 2006;Bernabucci et al, 2011;Singh et al, 2015). Identifying genes that repair AFB 1 -associated DNA damage could help identify which individuals are at elevated risk for HCC.…”
Section: Introductionmentioning
confidence: 99%